PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GRAHADIKA REALTY TANGERANG SELATAN - Dava Aria Wicaksana; Muhamad Guruh (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of motivation and work discipline on employee performance both partially and simultaneously. The method used is quantitative, with a total of 60 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The result of this study is that motivation has a significant effect on employee performance with the regression equation Y = 11.346 + 0.704X1. The value of the correlation coefficient of 0.744 means that both variables have a strong degree of relationship. The value of the coefficient of determination is 55.3%. Test the hypothesis obtained the value of t count > t table or (3.628 > 2.001). indicating that there is a significant influence between work motivation and employee performance Work discipline has a significant effect on employee performance with the regression equation Y = 12.422 + 0.682X2. The correlation coefficient value is 0.682, meaning that the two variables have a strong level of relationship. The coefficient of determination value is 50.3%. Hypothesis testing obtained a calculated t value > t table or (3.749 > 2.001). indicating that there is a significant influence between work discipline on employee performance. Motivation and work discipline have a significant effect on employee performance with the regression equation Y = 7,472 + 0,459X1 + 0,354X2. The value of the correlation coefficient or the degree of relationship between the independent variable and the dependent variable is obtained at 0.788, meaning that it has a strong level of relationship. The value of the coefficient of determination is 62.1%. Test the hypothesis obtained the value of F calculate > F table or or (46,685 > 3,16). indicating that there is a simultaneous significant influence between motivation and work discipline on employee performance.